When Lisbon met the Team 10 Cluster City - Borges, J. C.; Marat-Mendes, T. (Joelho: Revista de Cultura Arquitectónica, 2019)
After the Doorn Manifesto (1954), Team 10 members synthesize their earlier projects into a new urban model: the Cluster City. In 1961, the Lisbon Technical Office for Housing (Gabinete Técnico de Habitação) – GTH was established by the municipality to resolve an ongoing housing shortage. Soon, the GTH planned the urbanization of the Chelas Valley, an agricultural area in the East area of Lisbon. This plan tested approaches to neighbourhood planning unprecedented in the municipality. Its Zone I Plan, by Francisco Silva Dias and Luís Vassalo Rosa (1966) was the first to be implemented, echoing in practice the Doorn Manifesto. Here, we identify urban forms used in this Plan, and the ‘ground rules’ that structured it and influenced its change over time. Furthermore, we ask whether Chelas can shed some light in the recent demise of examples like Toulouse-Le Mirail and Robin Hood Gardens.